(untitled) (Experimental biology, 2015)
The major rivers of the desert south-eastern Kazakhstan are the Ile, Karatal, Aksu, Lepsy, Kaskelen, Sharyn, Shelek etc. 45 species of jewel beetles (Coleoptera, Buprestidae) of the 16 genera, belonging to 5 subfamilies: Julodinae (1 genus, 1 species, 2.2%), Polycestinae (2 genera, 6 species, 13.3%), Chrysochroinae (4 genera and 14 species, 31.1%), Buprestinae (4 genera, 8 species, 17.8 %), Agrilinae (5 genera, 16 species, 35.6%) are exposed in the floodplain habitats of desert rivers of South-East Kazakhstan. Sphenoptera (11 species), Agrilus (9 species), Acmaeoderella (5 species) genera are most richly represented. 56% species (28 species) of the fauna of jewel beetles in the floodplain habitats are rare. It include some species occasionally founds in riparian habitats, but are common in arid and semiarid habitats.